Fulfillment of the Right to Reduction of Prison Sentence for Drug Convicts - Amas Madina; Hartoyo Hartoyo; Fathul Hamdani; Fitri Ayuningtyas; Siti Marwiyah (Journal of International Multidisciplinary Research, 2025)
This study examines the fulfillment of remission rights for drug offenders in Indonesia following the enactment of Government Regulation No. 99 of 2012, which introduced restrictive provisions inconsistent with the rehabilitative vision of Law No. 12 of 1995. The research problem lies in the normative contradiction between correctional laws oriented toward behavioural reform and derivative regulations that prioritise punitive measures. The study aims to evaluate the implementation of remission regulations and their alignment with principles of justice and human rights. Employing a normative legal research design, it analyses statutes, judicial decisions, doctrines, and comparative law. Findings reveal that remission has shifted from a universal right to a conditional privilege, disproportionately affecting low-level drug offenders, exacerbating prison overcrowding, and weakening legal certainty. The study concludes that policy reform is necessary through individualised assessments, restorative justice integration, independent oversight, and regulatory harmonisation to restore fairness and uphold human rights.